2020
DOI: 10.1111/inr.12622
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethical work climate on the organizational citizenship behavior of academic nurses

Abstract: Aim: This study demonstrates the effect of academic nurses' perceptions of ethical work climate on their organizational citizenship behaviour. Background: Establishing healthy relationships in organizations and ensuring organizational effectiveness depend on workers' perception of organizational ethics and voluntary behaviours that improve their organizations. Methods: This study was conducted with 644 academic nurses working in public institutions of higher education that offer nursing education at the underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[ 6 ] As the important content of organizational behavior research, organizational citizenship behavior plays a significant role in improving employee loyalty, reducing separation rate, and stabilizing the nursing team. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] As the important content of organizational behavior research, organizational citizenship behavior plays a significant role in improving employee loyalty, reducing separation rate, and stabilizing the nursing team. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Lower job satisfaction and reduced organizational commitment caused by poor ethical issues are critical factors that could influence the organizational citizenship behavior of nurses [6] . As the important content of organizational behavior research, organizational citizenship behavior plays a significant role in improving employee loyalty, reducing separation rate, and stabilizing the nursing team [7] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is related to the implementation of ethical norms, which help build a work environment in which professionals follow ethical principles that support the quality of the health services they provide. In such workplaces, professionals practice ethical values that promote feelings of ownership and decrease feelings of loneliness, resulting in increased productivity and patient satisfaction with care [ 36 , 37 , 38 ]. Previous literature showed that numerous organizational and relational variables that contribute to creating a positive ethical climate can play a crucial role in protecting against moral distress.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of instruments that assess the quality of the work climate has been a focus of studies in this field. Certain authors have emphasized organizational characteristics [ 5 ], psychological features [ 6 ] and, in some cases, both [ 7 ].…”
Section: Introductionmentioning
confidence: 99%